Formulasi dan Evaluasi Fisik Sediaan Gel Antiseptik Tangan Dari Ekstrak Etanol 96% Daun Pandan Wangi (Pandanus Amaryllifolius Roxb) - Siti Marina; Banu Kuncoro; Sofi Nurmay Stiani; Rahmawida Putri (Journal of Pharmaceutical and Health Research, 2021)
Antiseptic serves to kill or inhibit the growth of bacteria that can cause the onset of disease. Antiseptics can be formulated with natural ingredients so that they are environmentally friendly. Pandan wangi leaf is a plant that is often used as a food additive leaves, as a green dye and aroma. Pandan fragrance is also one of the plants that can be used as antiseptic formulations because it has antibacterial activity and can be used as a topical preparation in the form of gels. The aim of this research is to know the difference of pandan wangi leaf extract concentration (Pandanus amaryllifolius Roxb.) Which has optimum physical properties evaluation. This research is an experimental research, maseration method used to get extract with 96% ethanol. The gel was formulated into four formulas with various extract concentrations of 10%, 20%, 30%, and 40%. Evaluation tests include: organoleptic, homogeneity, pH, dispersion, viscosity, stability, hedonic, irritation and hand antiseptic testing. The results showed that the concentration of extract had no effect on pH and homogeneity. Increased concentration of extract effect on the color change and aroma. The higher concentration of extract will be more concentrated also color. The result of stability inspection showed that texture change in F2 and aroma change in F3. A good gel preparation formula based on physical quality and hedonic test is a concentration formula of 10% (F1). Keywords: Pandanus amaryllifolius Roxb., Hand Antiseptic, Gel.